Brainstem tumors in children: a monocentric series in the light of genetic and bio-molecular progress in pediatric neuro-oncology - Boukaka, Rel Gerald; Beuriat, Pierre-Aurélien; Di Rocco, Federico; Vasiljevic, Alexandre; Szathmari, Alexandru; Mottolese, Carmine (Frontiers in Pediatrics, 2023)
Introduction Brainstem tumors represent a challenge. Their management and prognosis vary according to anatomopathological findings and genetic and bio-molecular fingerprints. We present our experience with pediatric brainstem tumors. Material and methods All patients admitted for a brainstem tumor at the Pediatric Neurosurgical Unit at Hôpital Femme Mère Enfant hospital between January 1997 and December 2019 were considered. Patients data were obtained through a retrospective review of the medical records; follow-up was from the last outpatient consultation. Results One hundred and twelve patients were included. Eighty-five patients (75.9%) had open surgery or stereotactic biopsy. Thirty-five patients were treated for hydrocephalus. Sixty-six received an adjuvant treatment. Several protocols were adopted according to the SFOP and SIOP during this time period. The overall survival rate was 45% with a median follow-up of five years (range 1–18 year). However, the survival rate was very different between the diffuse intrinsic pontine gliomas (DIPG) and the others tumor types. If we exclude the DIPG (59 patients), of which only 1 was alive at 3 years, the survival rate was 90.6% (only 5 deaths over 53 patients) with a median follow up of 5 years. Conclusions Our series confirms that benign tumors of the brainstem have a good survival when treated with surgical removal ± adjuvant therapy. Diffuse pontine gliomas continue to have a dismal prognosis. Individualized treatment based on molecular fingerprints may help to select the best adjuvant therapy and hence potentially improve survival.